The Impact of the Mediating Role of Organizational Loyalty on the Relation between Applying Social Responsibility Towards Human Resources and Employees Productivity in the Palestinian Universities in the Gaza Strip - AL-Ross , Sami; ALqasas , Hala (The Arab Journal of Administration, 2021)
The study aimed to identify the impact of the mediating role of organizational loyalty on the relation between applying social responsibility towards human resources and employees’ productivity in the Palestinian universities in the Gaza strip. The analytical descriptive approach was used through distributing a questionnaire using the stratified random sampling method that consisted of 330 individuals. The study found that there was positive agreement regarding the level of applying social responsibility towards human resources by universities, however, this agreement was not of high level. While the agreement was relatively higher regarding the level of organizational loyalty and the level of productivity. The results also showed that organizational loyalty has a strong significant impact as a mediating variable on the relationship between applying social responsibility towards human resources and the productivity of employees in Palestinian universities in the Gaza Strip. The results also showed that the older age groups, senior employees, and employees of Al Quds Open University have shown a higher appreciation for the application of social responsibility towards human resources, as well as, a higher level of organizational loyalty and productivity. The study recommended that the universities need to include social responsibility as part of its strategic plans, as well as its inclusion as part of the duties and responsibilities of a top level position or organizational unit in the university. Also, the universities need to fulfill their obligations towards employees to enhance organizational loyalty and raise productivity level. Moreover, activate the role of unions and guarantee the freedom of organized unionized activities aimed at protecting the rights and dignity of employees. In addition, to enhance universities commitment to the systems and legal references, and to the ethical code of conducts regulating the relationship between universities and employees.